EFFECT OF GRASS VETIVER AND STYLOSANTHES IN RESISTANCE PARAMETERS FROM THE SOIL TO THE SHEPHERD - Gomes, D. A. C.; Resende, G. M. C. S.; Dias, L. E. S.; Lima, P. L. T. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The shear strength of a soil mass is the internal resistance per unit area that this mass can offer to withstand ruptures and landslides along any plane in its interior. One of there is practices in the attempt to stabilize slopes involves the cultivation of different plant species. The objective of this work is to determine the parameters of soil shear strength (cohesion and angle of internal friction) of soil samples under the initial development of the vetiver grass. The effects on control (bare soil) and soil under vetiver grass cultivation will be evaluated through direct soil shear tests. The hypothesis of the work is that the vetiver grass will increase the resistance of the soil ensuring a stabilization of the slope. Consequently, no additional costs will be required with other higher cost containment works.